Molecular Detection of Candidatus Orientia chuto in Wildlife, Saudi Arabia - Alkathiry, Hadil A.; Alghamdi, Samia Q.; Morgan, Holly E.J.; Noll, Madeleine E.; Khoo, Jing J.; Alagaili, Abdulaziz N.; Makepeace, Benjamin L. (Emerging infectious diseases, 2023)
Scrub typhus is a zoonosis caused by 3 species of Orientia bacteria, including Candidatus Orientia chuto. This species is known only from a human case in Dubai and infections in wildlife in Kenya. We report molecular detection of Candidatus O. chuto in 2 wild rodent species from Saudi Arabia.